Preparation method of silane modified pure acrylic emulsion
The polymerization is initiated in aqueous solution by glow discharge electrolytic plasma technology to prepare silane-modified pure acrylic emulsion, which solves the shortcomings of existing pure acrylate emulsions in water resistance, pollution resistance, high and low temperature resistance, and achieves high thermal stability and wide application effects.
Patent Information
- Application Number
- CN202311343309.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-18
AI Technical Summary
The existing pure acrylate emulsions are weak in water resistance, pollution resistance, high and low temperature resistance, and have a high film forming temperature, which limits its application range.
The polymerization was initiated in aqueous solution by glow discharge electrolytic plasma technology, and silane-modified pure acrylic emulsion was prepared by one-step polymerization using monomers such as methyl methacrylate, butyl acrylate, acrylic acid and vinyl trimethoxysilane.
The thermal stability, calcium ion stability, adhesion and film formation of silane-modified pure acrylic emulsion are improved, the film formation temperature is reduced, and its application range is expanded.
Smart Images

Figure CN119842002A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating emulsion preparation, and in particular relates to a method for preparing a silane-modified pure acrylic emulsion. Background Art
[0002] Polyacrylate emulsion (pure acrylic emulsion for short) with cheap raw materials, simple process, excellent mechanical properties, good weather resistance and good film-forming properties is one of the most widely used polymer materials at present, and is often used in coatings, pressure-sensitive adhesives, textiles and other fields. However, its water resistance, pollution resistance, high and low temperature resistance are weak; in addition, its defects of becoming brittle at low temperatures and becoming sticky at high temperatures limit its application in many fields. The current research hotspot is to expand the application scope of pure acrylic emulsion by changing comonomers, emulsifiers and adding other modified substances.
[0003] Since silicone has strong bond energy and low surface energy of silicon-oxygen bond, and outstanding stability, antifouling, UV resistance, chemical corrosion resistance and other characteristics, using it to modify emulsion is one of the hot spots. The silane-modified system with Si-O-Si as the crosslinking point has significantly improved the gloss stability, waterproofness, weather resistance and anticorrosion performance of the coating, and the crosslinked film has good mechanical strength, hardness, solvent resistance, water resistance and wear resistance. The acrylate emulsion can be modified by silane to reduce the film-forming temperature of the emulsion and improve the water resistance, durability, antifouling and weather resistance of the coating. Common silicone monomers include vinyl triethyl silane (VTES), vinyl trimethoxy silane (VTMS) and methacryloxypropyl trimethoxy silane (KH570). Because they contain vinyl in their molecules, they can be copolymerized with acrylic monomers; at the same time, silicone monomers also contain ethoxy groups, which can form crosslinking points through their hydrolysis and condensation reactions, so they are commonly used silicone modifiers.
[0004] When preparing silane-modified emulsions, the traditional emulsion polymerization method is generally selected. The polymerization uses water as the medium and a low-molecular hydrophilic surfactant as the emulsifier. After the hydrophobic monomer is emulsified, an oil-in-water (O / W) emulsion system is formed, and the emulsion polymerization reaction is carried out under the action of a water-soluble initiator. The initiator is generally a thermal decomposition type or redox system of a water-soluble persulfate, such as ammonium persulfate, potassium persulfate, etc. Traditional free radical polymerization is formed by a series and parallel connection of free radical reactions such as chain initiation, chain growth, chain termination and chain transfer. Its advantages are mild polymerization environment, simple operation, easy mass production and industrialization, and applicable to a variety of polymerization methods and multiple types of monomers. At present, 65% to 75% of polymers are prepared by free radical polymerization mechanism. However, its disadvantage is that the reaction state, degree of polymerization and dispersibility of polymer compounds are difficult to control.
[0005] Glow discharge electrolysis is a new type of electrochemical method for producing low-temperature plasma. The phenomena occurring during glow discharge electrolysis are significantly different from those of ordinary electrolysis. Hickling et al. proposed that the chemical reactions induced by glow discharge electrolysis in aqueous solution are:
[0006] H2O + gas +nH2O→nOH·+nH·
[0007] H·+H·→H2
[0008] ·OH+·OH→H2O2
[0009] OH+H2O2→HO2+H2O
[0010] OH+HO2→H2O+O2
[0011] H·+·OH→H2O
[0012] Studies have shown that the most notable feature of glow discharge electrolysis is the non-Faraday characteristic (voltage greater than 320V, product yield seriously deviates from Faraday's law), that is, the amount of converted substances greatly exceeds the value calculated by Faraday's charge. 3+ When studying glow discharge electrolysis as a ·OH scavenger, it was found that about 12 mol of ·OH was generated in the liquid phase reaction zone for every 1 mol of electrons passing through, which far exceeded the yield calculated by Faraday's law. Since ·OH has high activity, it can undergo free radical addition reaction with organic monomers in solution. Although there are many reports on the use of glow discharge electrolytic plasma technology in the preparation of organic polymers, highly absorbent materials, and highly adsorbent hydrogels, there are no reports on its use in the preparation of emulsions. Summary of the invention
[0013] The object of the present invention is to provide a method for preparing a silane-modified pure acrylic emulsion. The prepared silane-modified pure acrylic emulsion has high thermal stability.
[0014] The technical solution adopted by the present invention is a method for preparing a silane-modified pure acrylic emulsion, which is specifically implemented according to the following steps:
[0015] Step 1, respectively weighing 2 to 10 parts of emulsifier, 35 to 75 parts of deionized water, 10 to 50 parts of methyl methacrylate, 10 to 30 parts of butyl acrylate, 1 to 5 parts of acrylic acid, 1 to 10 parts of vinyl trimethoxy silane and 0.5 to 5 parts of ammonia water;
[0016] Step 2, dissolving the emulsifier in deionized water, adding methyl methacrylate, butyl acrylate, acrylic acid and vinyl trimethoxysilane, stirring and emulsifying, cooling to room temperature, and obtaining a milky white pre-emulsion;
[0017] Step 3, using glow discharge electrolytic plasma technology to initiate polymerization of the pre-emulsion to obtain a polymerization product, filtering the polymerization product, and adjusting the pH to obtain a silane-modified pure acrylic emulsion.
[0018] The present invention is also characterized in that:
[0019] In step 1, the emulsifier is composed of sodium dodecyl sulfate and octylphenol polyoxyethylene ether, and the mass ratio of sodium dodecyl sulfate to octylphenol polyoxyethylene ether is 1-5:1-5.
[0020] In step 2, the stirring temperature is 40-60° C., and the stirring time is 1-2 h.
[0021] In step 3, specifically: at 25°C, with a platinum needle as an anode and a carbon rod as a cathode, the cathode and the anode are inserted into the pre-emulsion at the same time, the pre-emulsion is glow discharged at a voltage of 500-600V, the discharge is stopped, and the mixture is stirred in an oil bath and cooled to room temperature to obtain a polymerization product; the polymerization product is filtered through a 200-mesh sieve to remove the gel, and then the pH is adjusted to 7-8 with aqueous ammonia to obtain a milky white and bluish silane-modified pure acrylic emulsion.
[0022] The glow discharge time is 10 to 20 minutes.
[0023] The oil bath temperature is 70-110°C, the stirring time is 3-5h, and the stirring rate is 90-120r / min.
[0024] When the cathode and anode are inserted into the pre-emulsion, the distance between the cathode and the anode is 0.5 to 2.0 cm, and the depth of the cathode and the anode immersed in the pre-emulsion is 0.5 to 2.0 cm.
[0025] The diameter of the anode platinum needle is 0.3-0.8 mm, and the diameter of the cathode carbon rod is 3-7 mm.
[0026] The beneficial effects of the present invention are:
[0027] 1. In the method of the present invention, methyl methacrylate (MMA), butyl acrylate (BA), acrylic acid (AA) are used as soft, hard and functional monomers, vinyl trimethoxy silane (VTMS) is used as a silane modifier, sodium dodecyl sulfate (SDS) and octylphenol polyoxyethylene ether (OP-10) are used as emulsifiers, and glow discharge electrolytic plasma is used to initiate polymerization in an aqueous solution to obtain a silane-modified pure acrylic emulsion copolymer in one step, which has the advantages of easy raw material availability, simple preparation process, low synthesis cost, green reaction and environmental protection;
[0028] 2. In the method of the present invention, no initiator is required, no N2 protection is required, the reaction is controllable, and there is no secondary pollution;
[0029] 3. In the method of the present invention, the plasma initiation process is carried out at 25°C, which simplifies the initiation conditions of the silane-modified pure acrylic emulsion, shortens the initiation time, improves the purity of the emulsion, and enhances safety;
[0030] 4. The silane-modified pure acrylic emulsion synthesized by glow discharge electrolytic plasma has excellent calcium ion stability, weather resistance and adhesion;
[0031] 5. The prepared silane-modified pure acrylic emulsion has high thermal stability and is difficult to decompose below 300°C, so it has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a current-voltage curve diagram during the glow discharge electrolytic plasma initiation process of the preparation method of the present invention.
[0033] Figure 2 This is a transmission electron microscope (TEM) image of the silane-modified pure acrylic emulsion obtained in Example 1 of the preparation method of the present invention.
[0034] Figure 3 This is a particle size test chart of the silane-modified pure acrylic emulsion obtained in Example 1 of the preparation method of the present invention.
[0035] Figure 4 This is the Zeta potential diagram of the silane-modified pure acrylic emulsion obtained in Example 1 of the preparation method of the present invention.
[0036] Figure 5 This is the infrared spectrum of the silane-modified pure acrylic emulsion obtained in Example 1 of the preparation method of the present invention.
[0037] Figure 6 This is the XPS chart of the silane-modified pure acrylic emulsion obtained in Example 1 of the preparation method of the present invention.
[0038] Figure 7 This is the TG / DTG graph of the silane-modified pure acrylic emulsion obtained in Example 1 of the preparation method of the present invention.
[0039] Figure 8 This is the DSC graph of the silane-modified pure acrylic emulsion obtained in Example 1 of the preparation method of the present invention.
[0040] Fig. 9 This is a contact angle test diagram of the silane-modified pure acrylic emulsion obtained in Example 1 of the preparation method of the present invention. DETAILED DESCRIPTION
[0041] The present invention is described in detail below in conjunction with specific implementation modes and accompanying drawings.
[0042] The preparation method of the silane-modified pure acrylic emulsion of the present invention is specifically implemented according to the following steps:
[0043] Step 1, respectively weighing 2 to 10 parts of emulsifier, 35 to 75 parts of deionized water, 10 to 50 parts of methyl methacrylate, 10 to 30 parts of butyl acrylate, 1 to 5 parts of acrylic acid, 1 to 10 parts of vinyl trimethoxy silane and 0.5 to 5 parts of ammonia water;
[0044] Step 2, dissolving the emulsifier in deionized water, adding methyl methacrylate, butyl acrylate, acrylic acid and vinyl trimethoxysilane, stirring and emulsifying at 40-60° C. for 1-2 hours, cooling to room temperature, and obtaining a milky pre-emulsion;
[0045] The emulsifier is composed of sodium dodecyl sulfate (SDS) and octylphenol polyoxyethylene ether (OP-10), and the mass ratio of sodium dodecyl sulfate to octylphenol polyoxyethylene ether is 1-5:1-5;
[0046] When preparing the pre-emulsion, the mass ratio of the total mass of the monomer to the deionized water is 40-60:35-75.
[0047] Step 3, at 25° C., using a platinum needle as an anode and a carbon rod as a cathode, inserting the two electrodes into the pre-emulsion at the same time, using a high-voltage DC power supply, glow discharging the pre-emulsion at a voltage of 500-600V for 10-20 minutes, the purpose is to initiate emulsion polymerization; stopping the discharge, stirring at a rate of 90-120r / min for 3-5 hours in a 70-110° C. oil bath, cooling to room temperature, and obtaining a polymerization product; filtering the polymerization product with a 200-mesh sieve to remove gel, and then adjusting the pH to 7-8 with ammonia water to obtain a milky white and blue-light silane-modified pure acrylic emulsion;
[0048] When inserted into the pre-emulsion, the distance between the cathode and the anode is 0.5 to 2.0 cm, the depth of the cathode and cathode immersed in the liquid surface is 0.5 to 2.0 cm, the diameter of the anode platinum needle is 0.3 to 0.8 mm, and the diameter of the cathode carbon rod is 3 to 7 mm;
[0049] In the method of the present invention, methyl methacrylate (MMA), butyl acrylate (BA), and acrylic acid (AA) are used as raw materials, and vinyl trimethoxysilane (VTMS) is used as a modified monomer, and a one-step polymerization is initiated in an aqueous solution by using glow discharge electrolytic plasma. The method has the advantages of simple process (one-step completion), low cost (no nitrogen protection required), green and environmentally friendly (no secondary pollution), and no need to add initiator. The prepared silane-modified pure acrylic emulsion has excellent film-forming properties, thermal stability, and calcium ion stability, and is a polymer emulsion with excellent performance.
[0050] The structure and properties of the silane-modified pure acrylic emulsion prepared by the present invention are analyzed and explained below through the current-voltage curve, transmission electron microscopy, laser particle size test, Zeta potential, infrared spectrum, thermogravimetric analysis, and ion resistance test during the emulsion preparation process.
[0051] 1. Current-voltage curve
[0052] Figure 1 This is the current-voltage curve in the process of preparing silane-modified pure acrylic emulsion. In the AB section (0-300V) of the curve, the current increases with the increase of voltage, following Faraday's law of electrolysis and Ohm's law; in the BC section (300-360V), the water on the surface of the Pt needle evaporates under the action of Joule heat to produce a large number of steam bubbles. The steam bubbles are not conductive, so the resistance increases with the increase of voltage, resulting in unstable current and a significant decrease; in the CD section (360-400V), the bubbles on the surface of the Pt needle are broken down, generating a steam sheath and emitting a faint glow; in the DE section (400-700V), the steam sheath is completely broken down, the current tends to be stable with the increase of voltage, and the glow gradually increases, which is the normal discharge area. When the voltage is lower than 500V, the light generated is weak. When the discharge voltage is higher than 600V, the higher energy causes the anode platinum needle to melt and be damaged at high temperature. Therefore, the voltage range required for synthesizing silane-modified pure acrylic emulsion is 500-600V.
[0053] 2. Transmission electron microscopy test
[0054] Figure 2 The silane-modified pure acrylic emulsion was diluted with distilled water to a solid content of 0.2%, and then dripped onto a copper target. After being stained with 2% phosphotungstic acid, the internal morphology of the particles was observed using a U.S. JME-1200EX transmission electron microscope. Figure 2 It can be seen that the silane-modified pure acrylic emulsion is spherical, and the average particle size is about 115 nm.
[0055] 3. Emulsion particle size test
[0056] The particle size of the latex is one of the important factors affecting the specific surface area and viscosity of the latex. It is generally believed that the smaller the particle size, the larger the specific surface area of the latex particles, the greater the viscosity, and the better the adhesion. The particle size of the silane-modified pure acrylic latex particles was measured using the LA-960 laser particle size analyzer from HORIBA, Japan. Figure 3 It can be seen that the particle size of the silane-modified pure acrylic emulsion is unimodal, with a particle size distribution of 50-200 nm, and the average particle size measured by the particle size analyzer is about 110 nm. This result is basically consistent with the TEM test result, indicating that the emulsion has a small particle size and good adhesion.
[0057] 4. Zeta potential
[0058] Zeta potential can be used to evaluate the stability of the emulsion. When the absolute value of the zeta potential is greater than 30 mV, the stability is good. The Zeta potential of the silane-modified pure acrylic emulsion of the present invention was measured using a British Zetasizer NanoZS nanoparticle size analyzer. The results are shown in Figure 4 .Depend on Figure 4 It can be seen that the average zeta potential of the silane-modified pure acrylic emulsion is -71.7 mV, and its absolute value is much higher than 30 mV. Because the emulsifier used in the preparation method of the present invention is a composite emulsifier of anionic surfactant and nonionic surfactant, the composite emulsifier makes the surface of the emulsion particles negatively charged, so that the silane-modified pure acrylic emulsion has good stability.
[0059] 5. Infrared test
[0060] Pure acrylic emulsion and silane-modified pure acrylic emulsion were prepared by glow discharge electrolytic plasma, and then made into thin films. The structures of the two films were characterized by FTS 3000 Fourier transform infrared spectrometer (FT-IR) of DIGLAB Company, USA. The infrared spectra were shown in Figure 5 2956 and 2869cm -1 is the stretching vibration absorption peak of saturated CH, 1723 cm -1 The characteristic absorption peaks of carbonyl -C=O stretching vibration in methyl methacrylate and butyl acrylate are 1443 and 1385 cm -1 The peaks at 1232 and 1146 cm are the shear vibration absorption peaks of the CH bond. -1 The absorption peaks of COC in methyl methacrylate and butyl acrylate are at 1100-1000 cm due to the asymmetric stretching vibration of Si-O-Si. -1 and 809cm -1 New absorption peaks appear at 1650-1680cm, which are attributed to Si-O stretching vibration and Si-C stretching vibration, respectively. This shows that silane has been successfully grafted onto the emulsion chain. -1 and 895~885cm -1 The characteristic absorption band of C=C is at 40°. However, no absorption peak appears in this range in the infrared spectrum of the latex film, indicating that the unsaturated bonds of the reactive monomers fully participate in the copolymerization reaction to form a silicon-modified pure acrylic latex polymer.
[0061] 6. XPS test
[0062] The chemical structure of the silane-modified pure acrylic latex film was determined by XPS. Figure 7 It can be seen that the modified latex film has three peaks of C1s, O1s and Si2p, which appear at 284eV, 531eV and 102eV respectively, indicating that the functional monovinyltrimethoxysilane monomer is successfully grafted into the pure acrylic latex.
[0063] 7. Thermogravimetric test (TG)
[0064] The thermal stability of the silane-modified pure acrylic latex film was analyzed by using a TG / DSC-6 thermogravimetric-differential scanning calorimeter in a nitrogen atmosphere at a heating rate of 10°C / min from 20°C to 800°C. Figure 6 The thermogravimetric curve of the silane-modified pure acrylic emulsion is shown in Figure 1. It can be seen that the weight loss curve of the latex film can be divided into two stages: the film loses 6.79% of its weight at 100°C to 317°C, which is mainly due to the loss of mass of adsorbed and structural water and the loss of low molecular weight substances in the emulsion; the film loses 91.76% of its weight at 334°C to 500°C, which is due to the open chain rupture of the macromolecular chain in the film; and the final film mass remains 0.17%. It can be seen from the DTG curve that the film has an exothermic peak at a temperature of 419°C, which indicates that the silane-modified pure acrylic emulsion prepared by the preparation method of the present invention has good thermal stability.
[0065] 8. Differential Scanning Calorimetry (DSC)
[0066] Glass transition temperature (T g ) is one of the most important factors affecting the performance of emulsions. g The higher the value, the higher the rigidity of the latex chain, which may show better elasticity and cohesion. The glass transition temperature (T) of the silane-modified pure acrylic latex latex film was measured by differential scanning calorimetry (DSC, model 214Polyma, Netzsch Instruments, Germany). g 5-15 mg of the dried film was placed in a standard DSC sealed alumina crucible and the temperature was raised from -50 to 80°C at a heating rate of 10°C / min in a nitrogen atmosphere. Figure 8 This is the DSC curve of the latex film. It can be seen that there is only one characteristic endothermic peak (T g =-0.61°C), indicating that the film polymerization is complete.
[0067] 9. Contact angle test
[0068] The hydrophobicity of the silane-modified pure acrylic emulsion can be estimated by depositing water droplets on the film surface based on CA measurements, and the CA value depends on the chemical composition of the film surface. In addition, a higher CA value means that the film has a stronger hydrophobicity and better water resistance. The contact angle of the silane-modified pure acrylic emulsion was measured by the sessile drop method at room temperature using a contact angle meter (DSA100E, KYUSS, Germany). Fig. 9 As shown, for the silane-modified pure acrylic emulsion film prepared by glow discharge plasma initiation, its contact angle with water is about 62.3°, indicating that the film prepared by this method has a certain hydrophobicity.
[0069] 10. Stability test
[0070] 1) Centrifugal stability test: prepare emulsions with solid contents of 1%, 2%, and 3%, respectively, and then centrifuge them at 4000 r / min for 30 min to observe whether there is precipitation and stratification.
[0071] 2) Dilution stability: prepare emulsions with solid contents of 1%, 2%, and 3% respectively, and leave them at room temperature for 48 hours to observe whether the emulsions have precipitation and stratification.
[0072] 3) Ca 2+ Ionic stability: Use emulsions with solid contents of 1%, 2%, and 3% to prepare CaCl2 solutions with concentrations of 0.5% and 1.0%, then place them at room temperature for 48 hours to observe whether there is any stratification.
[0073] 4) Freeze-thaw stability test: Silane-modified pure acrylic emulsion samples with solid contents of 1%, 2%, and 3% were placed in a -17°C refrigerator for 8 hours, and then thawed at 20°C for 6 hours to observe whether the emulsion has stratification.
[0074] 5) Thermal stability test: Silane-modified pure acrylic emulsions with solid contents of 1%, 2%, and 3% were sealed and then placed in a 60°C oven for 48 hours, cooled to room temperature, and observed for stratification.
[0075] Example 1
[0076] Add 60g of deionized water and 2.5g of a composite emulsifier (SDS and OP-10 are added in a mass ratio of 1:1) into a 250mL three-necked flask, stir to fully dissolve the emulsifier, then add 23g of methyl methacrylate, 23g of butyl acrylate, 1g of acrylic acid monomer and 1g of vinyltrimethoxysilane-modified monomer, stir and emulsify at 50°C for 60min, cool to room temperature, and obtain a milky white pre-emulsion; insert two electrodes into the pre-emulsion at 25°C, connect the circuit, and glow discharge at 500V for 15min; stop the discharge, stir at 90r / min in a 90°C oil bath for 5h, cool to room temperature, and obtain a polymerization product; filter the polymerization product with a 200-mesh sieve to remove the gel, and then adjust the pH to 7-8 with ammonia water to obtain a milky white, bluish silane-modified pure acrylic emulsion.
[0077] Example 1 The performance indicators of the silane-modified pure acrylic emulsion prepared were: solid content 33.1%, conversion rate 82.5%, gel rate 1.23%, stability (Ca 2+ The ionic stability, centrifugal stability, thermal stability, and freeze-thaw stability are good, and the average particle size of the emulsion is about 115 nm.
[0078] Example 2
[0079] Add 50g of deionized water and 3g of composite emulsifier (SDS / OP-10 added at a mass ratio of 1:1) to a 250mL three-necked flask, stir to fully dissolve the emulsifier, add 30g of methyl methacrylate, 20g of butyl acrylate, 1g of acrylic acid monomer and 3g of vinyl trimethoxysilane modified monomer, stir and emulsify at 40°C for 90min, cool to room temperature, and obtain a milky white pre-emulsion. Insert two electrodes into the pre-emulsion at 25°C, connect the circuit, and perform glow discharge at 520V for 10min; stop the discharge, stir at 120r / min in an 80°C oil bath for 3h, cool to room temperature, and obtain a polymer product; filter the polymer product with a 200-mesh sieve to remove the gel, and then adjust the pH to 7-8 with ammonia water to obtain a milky white, blue-light silane-modified pure acrylic emulsion.
[0080] Example 2 Performance indicators of the silane-modified pure acrylic emulsion: solid content 33.9%, conversion rate 83.4%, gel rate 1.29%, stability (Ca 2+ The ionic stability, centrifugal stability, thermal stability, and freeze-thaw stability are good, and the average particle size of the emulsion is about 97.8 nm.
[0081] Example 3
[0082] Add 55g of deionized water and 3g of composite emulsifier (SDS / OP-10 is added at a mass ratio of 1:1) to a 250mL three-necked flask, stir to fully dissolve the emulsifier, add 35g of methyl methacrylate, 12g of butyl acrylate, 2g of acrylic acid monomer and 5g of vinyl trimethoxysilane modified monomer, stir and emulsify at 60°C for 120min, cool to room temperature, and obtain a milky white pre-emulsion. Insert two electrodes into the pre-emulsion at 25°C, connect the circuit, and perform glow discharge at 540V for 20min; stop the discharge, stir at a speed of 105r / min for 4h in a 110°C oil bath, cool to room temperature, and obtain a polymer product; filter the polymer product with a 200-mesh sieve to remove the gel, and then adjust the pH to 7-8 with ammonia water to obtain a milky white, blue-light silane-modified pure acrylic emulsion.
[0083] Example 3 Performance indicators of the silane-modified pure acrylic emulsion: solid content 28.8%, conversion rate 85.1%, gel rate 1.7%, stability (Ca 2+ The ionic stability, centrifugal stability, thermal stability, and freeze-thaw stability are good, and the average particle size of the emulsion is about 110.3 nm.
[0084] The method of the present invention generates highly active species such as ·OH, ·H, ·O, H2O2, etc. around the needle-shaped electrode by tip discharge, and uses free radicals to initiate chain addition to prepare silane-modified pure acrylic emulsion. It has the advantages of simple process (completed in one step), low cost (no nitrogen protection required), green and environmentally friendly (no secondary pollution), and no need to add initiator.
Claims
1. A method for preparing a silane-modified pure acrylic emulsion, characterized in that: Follow the steps below to implement it: Step 1, respectively weighing 2 to 10 parts of emulsifier, 35 to 75 parts of deionized water, 10 to 50 parts of methyl methacrylate, 10 to 30 parts of butyl acrylate, 1 to 5 parts of acrylic acid, 1 to 10 parts of vinyl trimethoxy silane and 0.5 to 5 parts of ammonia water; Step 2, dissolving the emulsifier in deionized water, adding methyl methacrylate, butyl acrylate, acrylic acid and vinyl trimethoxysilane, stirring and emulsifying, cooling to room temperature, and obtaining a milky white pre-emulsion; Step 3, using glow discharge electrolytic plasma technology to initiate polymerization of the pre-emulsion to obtain a polymerization product, filtering the polymerization product, and adjusting the pH to obtain a silane-modified pure acrylic emulsion.
2. The method for preparing the silane-modified pure acrylic emulsion according to claim 1, characterized in that: In the step 1, the emulsifier is composed of sodium dodecyl sulfate and octylphenol polyoxyethylene ether, and the mass ratio of sodium dodecyl sulfate to octylphenol polyoxyethylene ether is 1-5:1-5.
3. The method for preparing the silane-modified pure acrylic emulsion according to claim 1, characterized in that: In the step 2, the stirring temperature is 40 to 60° C., and the stirring time is 1 to 2 hours.
4. The method for preparing the silane-modified pure acrylic emulsion according to claim 1, characterized in that: In the step 3, specifically: at 25° C., using a platinum needle as an anode and a carbon rod as a cathode, inserting the cathode and the anode into the pre-emulsion at the same time, performing glow discharge on the pre-emulsion at a voltage of 500 to 600 V, stopping the discharge, stirring in an oil bath, and cooling to room temperature to obtain a polymer product; The polymerized product was filtered through a 200-mesh sieve to remove the gel, and then the pH was adjusted to 7-8 with aqueous ammonia to obtain a milky white and bluish silane-modified pure acrylic emulsion.
5. The method for preparing the silane-modified pure acrylic emulsion according to claim 4, characterized in that: The glow discharge time is 10 to 20 minutes.
6. The method for preparing the silane-modified pure acrylic emulsion according to claim 4, characterized in that: The oil bath temperature is 70-110°C, the stirring time is 3-5h, and the stirring rate is 90-120r / min.
7. The method for preparing the silane-modified pure acrylic emulsion according to claim 4, characterized in that: When the cathode and the anode are inserted into the pre-emulsion, the distance between the cathode and the anode is 0.5 to 2.0 cm, and the depth of the cathode and the anode immersed in the pre-emulsion is 0.5 to 2.0 cm.
8. The method for preparing the silane-modified pure acrylic emulsion according to claim 4, characterized in that: The diameter of the anode platinum needle is 0.3-0.8 mm, and the diameter of the cathode carbon rod is 3-7 mm.
Citation Information
Patent Citations
Carbon nano-tube modified by in-situ polymerization based on plasma initiation and preparation method thereof
CN101559936A
Waterborne silicone acrylate emulsion with core-shell structure and preparation method of waterborne silicone acrylate emulsion
CN107226883A